Chinese and western medicine treatment of myocardial fibrosis drugs - Yuxi Zhu; Yuxi Zhu; Fangmei Zhang; Zhongcheng Li; Yu Zhou; Yi Shu; Jian Ruan; Guo Chen (Frontiers in Cardiovascular Medicine)
Myocardial fibrosis (MF) is a common pathological manifestation of many cardiovascular diseases, such as myocardial infarction, myocardial ischemia, and sudden cardiac death. It is characterized by excessive proliferation and activation of fibroblasts, transformation into myofibroblasts, and, eventually, excessive deposition of the extracellular matrix, resulting in heart damage. Currently, modern drugs such as angiotensin-converting enzyme inhibitors, diuretics, and β-blockers can improve myocardial fibrosis in clinical treatment, but their therapeutic effect on this disease is limited, with obvious side effects and high cost. Traditional Chinese medicine (TCM) has the advantages of multiple targets, low cost, and few side effects. Traditional Chinese medicines, such as Salvia miltiorrhiza, Astragalus, and Angelica extracts, and patent Chinese medicines, such as Qiliqiangxin capsules, Shenqi Yiqi dropping pills, and Tongxinluo capsules, can improve myocardial fibrosis. In this review, current Chinese and Western medicine methods for treating myocardial fibrosis are discussed. The signaling pathways and targets of Chinese and Western medicine are involved in the treatment of myocardial fibrosis. This review aimed to provide valuable insights and ideas for both clinical treatment and basic research on myocardial fibrosis.